IMPLEMENTATION OF OMNIBUS MODEL REGULATIONS IN THE ESTABLISHMENT OF REGIONAL REGULATIONS - Mery Herlina (Fox Justi : Jurnal Ilmu Hukum, 2023)
Currently, the formation of laws and regulations using the omnibus method has been accommodated in the system of laws and regulations in Indonesia. The problem is how to apply it to regional regulations? This research is legal research (legal research) with a typology of normative legal research or doctrinal research that aims to produce arguments, theories, or new concepts for solving the problems to be studied. The results of the study concluded that the application of the omnibus model regulation in the formation of regional regulations can be carried out on the substance of the contents of regional regulations whose formation provisions are based on the implementation of laws formed using the omnibus law method. In addition, the application of the omnibus model regulations in the formation of Regional Regulations are intended to solve various problems in the formation of the Regional Regulations themselves, mainly with regard to the increasing number and inconsistent and harmonious contents.